2012
DOI: 10.1016/j.ijid.2011.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of retinopathy in Egyptian patients with chronic hepatitis C virus treated with pegylated interferon plus ribavirin

Abstract: Retinopathy associated with interferon α-2a and ribavirin combination therapy tends to develop in patients of older age with hypertension and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Also, we found that 6 patients of IFN-induced retinopathy were non-responders (failed to achieve ETR) which was similar to that reported by Fouad et al (25).…”
Section: Discussionsupporting
confidence: 91%
“…Also, we found that 6 patients of IFN-induced retinopathy were non-responders (failed to achieve ETR) which was similar to that reported by Fouad et al (25).…”
Section: Discussionsupporting
confidence: 91%
“…1 Twelve patients treated for chronic hepatitis B infection were excluded from the incidence data shown; 2 Sixteen patients treated for chronic hepatitis B infection were excluded from the incidence data shown; 3 Three patients that had baseline diabetic retinopathy were excluded from the incidence data shown. [28] 22 of 84 (26%) Egypt Baseline, 12, 24 and 48 wk and 1 mo after completing treatment IAR: no reduced VA in eyes that developed IAR. Three patients with IAR developed retinal hemorrhages and treatment was ceased.…”
Section: How Common Is Interferon-associated Retinopathy?mentioning
confidence: 97%
“…Older age has been suggested to represent a greater risk for its development, but this has not been a consistent finding [17,19,22,29] . The larger studies that assessed risk factors identified above did not implicate age, with the exception of Fouad et al [28] , Vujosevic et al [29] , Mehta et al [31] and Kim et al [32] . An association of age with the development of interferon-associated retinopathy may be because it is also associated with a higher risk of diabetes and hypertension.…”
Section: Are There Any Groups That Are At Greater Risk For Developingmentioning
confidence: 99%
See 2 more Smart Citations